Transconversações queer: sussurros e gemidos lusófonos Quatro cadelas mirando a(s) Psicologia(s) - Peres, Wiliam Siqueira; Pocahy, Fernando Altair; Carneiro, Nuno Santos; Teixeira Filho, Fernando Silva [UNESP] (My University, 2014)
To follow the cartographies’ path throughout pernicious (dis)courses of the capitalized Psychology. Com/positions both around desires and binary desires raised from binary norms, followed by (un)folding the beds, the “family”, the clinical thought and practice, the research, the geni(t)ality. Profane writing. Epistemic micro-rebellion promised and incorporated by the ass, because in the beginning it was and it (also) is the ass. A distorted and a trans-barked way of writing by four female dogs looking at Psychology. To (d)enounce the ménage that psychologists, supported by a history without history, intent to build over their empty beds which are blemished by modern Truth(s). Towards a minor psychology, this is a schizo-queer-analytic manifesto on desires-pleasures-senses within the lusophone transcontemporaneity. In the absence of a conclusion, we propose rather the provocative state that only a bitchy-psychology-to-come could edify the visibility of the invisible human. Otherwise, we believe it is in the promising barks that Psychology can be withdrawn from its betraying and betrayed contention of multitudes

Seguir rastro às cartografias em (dis)cursos nefastos da maiusculizada Psicologia. Com/posições dos desejos e desejos binários de binárias normas, para depois (dis)torcer as camas, a “família”, a clínica, a pesquisa, a geni(t)alidade. Escrita profana. Micro-rebelião epistemológica que o cu (pro)mete, porque no começo era e é (também) o cu. Um escrever torcido e trans-latido entre quatro cadelas mirando a Psicologia. (D)enunciar aqui o ménage que psis, numa história sem história, intentam em seus leitos vazios manchados da(s) Verdade(s) moderna(s). Por uma psicologia menor, manifesto esquizo-queer-analítico dos desejos-prazeres-sentidos na/da transcontemporaneidade lusófona. No lugar de uma conclusão, propomos a provocação de que só uma psicologia-em-devir-acadelado possa construir visibilizações do invisiblizado humano. Ou os latidos que acreditamos promissores para que se retire a Psicologia da sua traidora e traída contenção das multitudes.
Keywords: Transcontemporaneidade; Psicologia e Teoria Queer; Processos de Subjetivação; Desconstrucionismo; Políticas Anais